Unification of vertical datum in Sabah and Sarawak - Othman, Anuar H. (Penerbit UTM Press, 2014)
The present vertical datums in Sabah and Sarawak (East Malaysia) are based upon various tide gauge measurements of mean sea level over certain period defined locally, are manifested by a physical framework of vertical reference point i.e benchmarks. An effort to establish a unified vertical network in Sabah and Sarawak has undergone very tedious survey operation, lack of access routes to connect levelling network due to geographical setting constraint, and it is too costly to be fully implemented. This paper discussed the current status of vertical datum in East Malaysia as well as the concept of realizing new vertical datum based on gravimetric geoid model.